2000
DOI: 10.1046/j.1468-1331.2000.t01-1-00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum soluble E‐selectin and antisulfoglucuronyl paragloboside antibodies in amyotrophic lateral sclerosis

Abstract: Immunological abnormality is often found in amyotrophic lateral sclerosis (ALS). Antibodies to sulfoglucuronyl paragloboside (SGPG) were reported in ALS, although the pathogenetic significance of the antibodies is still unknown. We have already demonstrated that SGPG, a unique glycolipid, is present in both peripheral nerve and vascular endothelial cells. To investigate whether serum anti-SGPG antibodies would participate in activation and/or injury of endothelial cells in ALS, we examined serum anti-SGPG anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
4
1
Order By: Relevance
“…However, occasionally patients with motor neuron disorders or clinically similar neuropathies have responded to immunosuppressive therapy [60][61][62]. Our study has not confirmed the results of a recent study [26] dealing with the role of E-selectin in ALS. The nonincreased levels of s-ICAM and s-E-selectin in our patients do not implicate endothelial activation and probably cytokine's production in the pathogenesis of ALS.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However, occasionally patients with motor neuron disorders or clinically similar neuropathies have responded to immunosuppressive therapy [60][61][62]. Our study has not confirmed the results of a recent study [26] dealing with the role of E-selectin in ALS. The nonincreased levels of s-ICAM and s-E-selectin in our patients do not implicate endothelial activation and probably cytokine's production in the pathogenesis of ALS.…”
Section: Discussioncontrasting
confidence: 94%
“…Serum and cerebrospinal fluid (CSF) immunological findings were analyzed [25], and elevated CSF IgG index, higher incidence of immune complexes, complement involvement and CSF oligoclonal bands were reported. Recently, an elevation of serum soluble E-selectin associated with antibodies to sulfoglucuronyl paragloboside (SGPG) was reported in patients with ALS [26]. These results are an evidence of endothelial cell activation in some ALS patients.…”
Section: Introductionmentioning
confidence: 97%
“…Sulfoglucuronosyl paragloboside (SGPG) is one of the glycolipid target antigens in various peripheral neuropathies ( Leger et al., 1996 ). Anti-SGPG antibody has been reported by us as well as other groups to be present in the serum samples of some ALS patients ( Maeda et al., 1991 ; Ben Younes-Chennoufi et al., 1995 ; Ikeda et al., 2000 ). However, its involvement in the neuropathogenesis of ALS has not been studied in a large number of patients with well-documented clinical and demographic records, which precludes its clinical significance.…”
Section: Introductionmentioning
confidence: 60%
“…In our studies with patients having multiple sclerosis, we demonstrated elevated levels of intrathecal anti‐NFM [13]. The immune response is not only directed against cytoskeletal structures, but also other neuron components such as gangliosides [3,16,17].…”
Section: Discussionmentioning
confidence: 99%